Establishing Thromboelastography with Platelet-Function Analyzer Reference Ranges and Other Measures in Healthy Term Pregnant Women - Antony, Kathleen M.; Mansouri, Roshanak; Arndt, Melanie; Rocky Hui, Shiu-Ki; Jariwala, Purviben; Mcmullen, Virginia Moreland; Teruya, Jun; Aagaard, Kjersti (American Journal of Perinatology, 2015)
Objective The diagnosis of coagulopathy cannot always be performed at point of care. Thromboelastography (TEG) and the platelet-function analyzer (PFA-100), have emerged as reliable means for coagulation analysis. However, their reliable utility in pregnancy remains to be determined. We sought to establish reference values with concomitant determination of other known coagulation measures in nonlaboring gravidae in an effort to report the mean and variance of multiple testing modalities.Study Design Fifty-nine term, nonlaboring, pregnant women without comorbidities were enrolled, either at presentation for scheduled delivery or at presentation to triage for a non–labor-related indication. TEG, PFA-100, and complete coagulation measures of the overall hemostatic function (including prothrombin time, activated partial thromboplastin time, fibrinogen, protein C, protein S, von Willebrand factor antigen, ristocetin cofactor activity, and ADAMTS-13) were performed. Prior investigations of TEG and PFA-100 parameters in normal gravidae were reviewed, and pooled means and standard deviations (as a measure of variance) were calculated.Results TEG and PFA-100 parameters were significantly different among pregnant gravidae compared with nonpregnant reference ranges, and varied in association with other measures of the coagulation system. Our results and the pooled results reflect a hypercoagulable state.Conclusion Our data suggest that TEG values are significantly different in term, nonlaboring, healthy gravidae compared with nonpregnant reference values. Pooled means and standard deviations shown here may be considered for reference.
Keywords: thromboelastography; platelet-function analyzer; pregnancy; reference values